A retrospective study of 323 total laparoscopic hysterectomy cases for various indications and a case report treating caesarean scar pregnancy - Isono, Wataru (J Med Case Rep, 2020)
BACKGROUND: The application of laparoscopic surgeries has been increasing, and various uterine diseases in addition to leiomyoma/adenomyoma have become indications for total laparoscopic hysterectomy (TLH). Therefore, data acquisition and analysis of TLH procedures, including TLH for rare uterine diseases, have become important for improving surgical procedures and patient selection. To determine the prevalence of and risk factors for the occurrence of intraoperative and postoperative complications of TLH, we performed a multivariate analysis of the records in our hospital. METHODS: We retrospectively reviewed the medical records of 323 patients who underwent TLH for the treatment of leiomyoma/adenomyoma (278 cases), low-grade (pre)malignant uterine tumours (40 cases) and other rare uterine diseases (5 cases) from January 1, 2015, to December 31, 2019. Of the rare uterine diseases, one case of caesarean scar pregnancy for which TLH was performed is introduced as a case report. To assess the effects of 11 representative factors, including patient characteristics, uterus and leiomyoma sizes, indications for TLH and others, we performed a multivariate logistic regression analysis. RESULTS: Among the 323 cases, 20 intraoperative complications and 15 postoperative complications were reported. In the multivariate analysis, “ovarian tumour” and “heavy uterus” were positively associated and “nulliparity” was negatively associated with intraoperative complications. There were no significant risk factors for postoperative complications. The only risk factor for operative complications directly related to the resected uterus was “heavy uterus”. Therefore, we could perform TLH relatively safely for patients with other indications besides leiomyoma/adenomyoma. CONCLUSIONS: Considering the factors detected in this analysis, the indications for TLH may be expanded. Owing to the increase in TLH for indications other than leiomyoma/adenomyoma, a more accurate determination of the treatment approach can be achieved.